100 years of fashion illustration - Blackman, Cally; Laurence King Publishing (London : Laurence King, 2007)
In this book, Cally Blackman provides a visual feast of 400 dazzling images. The book offers an overview of the development of fashion, as seen through the eyes of the greatest illustrators of the day.
Introduction -- 1900-1924 -- 1925-1949 -- 1950-1974 -- 1975 and beyond -- List of illustrators -- Index -- Picture credits and acknowledgements.
Includes bibliographical references (pages 379) and index.
Keywords: Fashion drawing -- History -- 20th century; Fashion -- History -- 20th century -- Pictorial works